Mother-to-child transmission of oncogenic polyomaviruses BKPyV, JCPyV and SV40. Issue 5 (May 2020) - Mazzoni, Elisa; Pellegrinelli, Elena; Mazziotta, Chiara; Lanzillotti, Carmen; Rotondo, John Charles; Bononi, Ilaria; Iaquinta, Maria Rosa; Manfrini, Marco; Vesce, Fortunato; Tognon, Mauro; Martini, Fernanda
Highlights: BK (BKPyV), JC (JCPyV) and simian virus 40 (SV40) polyomaviruses were investigated for their vertical transmission. PyV footprints were analysed by the digital droplet PCR and indirect E.L.I.S.As with viral mimotopes. PyV sequences and IgG antibodies were detected, with a different prevalence, in pregnant females and newborns. PyV vertical transmission from females to offspring was revealed suggesting a potential risk of diseases in newborns. Summary: Objectives: Polyomavirus (PyV) infections have been associated with different diseases. BK (BKPyV), JC (JCPyV) and simian virus 40 (SV40) are the three main PyVs whose primary infection occurs early in life. Their vertical transmission was investigated in this study. Methods: PyV sequences were analyzed by the digital droplet PCR in blood, serum, placenta, amniotic fluid, vaginal smear from two independent cohorts of pregnant females and umbilical cord blood (UCB) samples. IgG antibodies against the three PyVs were investigated by indirect E.L.I.S.As with viral mimotopes. Results: DNAs from blood, vaginal smear and placenta tested BKPyV-, JCPyV- and SV40-positive with a distinct prevalence, while amniotic fluids were all PyVs-negative. A prevalence of 3%, 7%, and 3% for BKPyV, JCPyV and SV40 DNA sequences, respectively, was obtained in UCBs. Serum IgG antibodies from pregnant females reached an overall prevalence of 62%, 42% and 17% for BKPyV, JCPyV and SV40, respectively. Sera from newborns (UCB) tested IgG-positive with a prevalence of 10% for BKPyV/JCPyV and 3% for SV40. Conclusions: In this investigation, PyV vertical transmission was revealed by detecting PyV DNA sequences and IgG antibodies in samples from females and their offspring suggesting a potential risk of diseases in newborns. Graphical abstract: Image, graphical abstract